Medical outcomes of bromethalin rodenticide exposures reported to US poison centers after federal restriction of anticoagulants. (2nd November 2019) - Feldman, Ryan; Stanton, Matthew; Borys, Douglas; Kostic, Mark; Gummin, David
Abstract: Background: Exposures to bromethalin rodenticides have increased since restrictions were placed on long acting anticoagulant rodenticide (LAAR) registrations in 2008. Bromethalin works, in part, by uncoupling mitochondrial oxidative phosphorylation. Toxicity in humans is not well characterized and no antidote is available. Methods: This retrospective observational study analyzed data from the National Poison Data System (NPDS). The data set was derived from single substance bromethalin ingestions followed to a known medical outcome that were reported to US poison centers from 01/01/2008 to 12/31/2017. Results: There were 2674 bromethalin exposures in the NPDS database that met inclusion criteria. Of these exposures 2227 (83.28%) were pediatric, aged 16 days–12 years. Within this population, no effects were seen in 2143 (96.38%) of the exposures, 74 (3.32%) had minor effects, and 10 (0.45%) had moderate effects. No major clinical effects or deaths occurred in pediatric patients, although one patient with a major effect was of unknown age. Exposures in patients >12 years encompassed 391 patients aged 13–94 years. No effect was seen amongst 257 (65.73%) of the patients, 100 (25.58%) had minor effects, 23 (5.88%) had moderate effects, nine (2.30%) had major effects, and two (0.51%) patients died. Intentional ingestions among these patients accounted for one (0.25%) death and four (1.02%) major effects. Case details of the intentional ingestion death suggest the possibility of a miscoded long acting coagulant rodenticide. Conclusions: No major effects or deaths were seen in pediatric exposures. A majority of the possible bromethalin exposures involving adults reported to poison centers resulted in minor or no effects, though seizures, death and one questionable case of coagulopathy were documented. This dataset suffers from its retrospective nature, reliance on caller information, selection bias, information bias, and miscoding. It is possible that one or both deaths attributed to bromethalin exposure were not actually due to bromethalin.